2010
DOI: 10.3109/02713680903447892
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Error May Influence Mesopic Pupil Size

Abstract: This study showed that age and magnitude of both spherical and cylindrical refractive error are the most determinative factors on mesopic pupil size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 19 publications
(14 reference statements)
5
27
0
1
Order By: Relevance
“…The results from our study are in agreement with two earlier studies conducted on preoperative refractive surgery candidates 8,9. Cakmak et al and Linke et al reported significant differences in pupil size according to both age (smaller pupils with increasing age) and refractive error (smaller pupils in hyperopes than myopes); however, in their studies, measurements were only conducted under mesopic conditions, whereas our study was conducted at three luminance levels representing those commonly encountered during day-to-day activities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results from our study are in agreement with two earlier studies conducted on preoperative refractive surgery candidates 8,9. Cakmak et al and Linke et al reported significant differences in pupil size according to both age (smaller pupils with increasing age) and refractive error (smaller pupils in hyperopes than myopes); however, in their studies, measurements were only conducted under mesopic conditions, whereas our study was conducted at three luminance levels representing those commonly encountered during day-to-day activities.…”
Section: Discussionsupporting
confidence: 93%
“…More recently, the role of refractive status on pupil size has been investigated in several refractive surgery studies. Although no relationship was found in one study with a relatively small sample size,7 two larger studies of refractive surgery candidates reported that the preoperative refractive status was found to be a determinative factor in pupil size when measured under mesopic conditions, with smaller pupil sizes reported for hyperopes than myopes 8,9…”
mentioning
confidence: 94%
“…Pupil size correlates with both the magnitude and orientation of astigmatism. Larger mesopic pupil sizes are detected with higher cylinder powers and are also associated with with-the-rule astigmatism rather than against-the-rule and oblique astigmatism (Cakmak et al, 2010). Larger pupil sizes-in low lighting conditions-increase the amount of higher order aberrations such as coma and may intensify the cylinder power in subjective/manifest refraction.…”
Section: Pupil Dynamicsmentioning
confidence: 95%
“…We thank the authors for bringing additional articles investigating the relationship between pupil diameter and refractive error to our attention [2][3][4][5] . These articles were not omitted as a result of an incomplete literature search, as suggested by Guillon et al; they were omitted from our citations because the methodology in these studies meant that they were not comparable to our study and therefore their inclusion would have been inappropriate.…”
mentioning
confidence: 99%
“…We also feel that it is unsatisfactory to cite conference abstracts in peer reviewed papers as the source data is not easily verifiable 5 . The data from all of the omitted studies [2][3][4][5] were collected under mesopic illumination conditions which, although relevant in the context of refractive surgery, are not comparable to our study in which we deliberately examined pupil diameter over a wide photopic illumination range. This is due to the fact that the influence of the accommodation response, which was central to our study, would not have been accurate in mesopic conditions and would have likely fallen to tonic resting levels.…”
mentioning
confidence: 99%